Tregs in transplantation tolerance: role and therapeutic potential - Cassano, Alexandra; Chong, Anita S.; Alegre, Maria-Luisa (Frontiers in Transplantation, 2023)
CD4 + Foxp3 + regulatory T cells (Tregs) are indispensable for preventing autoimmunity, and they play a role in cancer and transplantation settings by restraining immune responses. In this review, we describe evidence for the importance of Tregs in the induction versus maintenance of transplantation tolerance, discussing insights into mechanisms of Treg control of the alloimmune response. Further, we address the therapeutic potential of Tregs as a clinical intervention after transplantation, highlighting engineered CAR-Tregs as well as expansion of donor and host Tregs.